The Use of Phraseological Units in the Novel "Qoraquyun" (Zien Journal of Social Sciences and Humanities, 2022)
The more expressive and effective our thoughts are, the more likely it is that we will be able to use a one-word phrase correctly. Appropriate use of phrases increases the chances of understanding the information being conveyed to the listener. A phrase is the second linguistic unit in the lexical stage of language construction, consisting of a semantic-syntactic combination of more than one lexeme, hence a compound segment unit. In the literature, this linguistic unit is referred to by terms such as phraseology, phraseological unit. Based on the main evidence, this study will help to solve some of the problems related to phrasal verbs.